A French Real-World Evidence Study Evaluating the Efficacy, Safety, and Pharmacokinetic Parameters of rVIII-SingleChain in Patients with Hemophilia A Receiving Prophylaxis - Guillet, Benoit; Hassoun, Abel; Wibaut, Bénédicte; Harroche, Annie; Biron-Andréani, Christine; Repesse, Yohan; d'Oiron, Roseline; Tardy, Brigitte; Pan Petesch, Brigitte; Chamouni, Pierre; Gay, Valérie; Fouassier, Marc; Pouplard, Claire; Martin, Cédric; Catovic, Hasan; Delavenne, Xavier (Thrombosis and Haemostasis, 2023)
Background rVIII-SingleChain is a recombinant factor VIII (FVIII) with increased binding affinity to von Willebrand factor compared with other FVIII products. rVIII-SingleChain is indicated for the treatment and prevention of bleeding episodes in patients with hemophilia A.Objectives To collect real-world evidence data from patients treated with rVIII-SingleChain to confirm the efficacy and safety established in the clinical trial program and carry out a population pharmacokinetic (PK) analysis.Methods This interim analysis includes data, collected between January 2018 — September 2021, from patients treated with rVIII-SingleChain prophylaxis at French Hemophilia Treatment centers. Data on annualized bleeding rates, dosing frequency, and consumption before and after switching to rVIII-SingleChain were recorded. A population PK analysis was also conducted to estimate PK parameters.Results Overall, 43 patients switched to prophylaxis with rVIII-SingleChain either from a previous prophylaxis regimen or from on-demand treatment. Following the switch to rVIII-SingleChain, patients maintained excellent bleed control. After switching to rVIII-SingleChain, most patients maintained or reduced their regimen. Interestingly, a majority of patients treated >2 ×/weekly with a standard half-life FVIII reduced both injection frequency and FVIII consumption with rVIII-SingleChain. A PK analysis revealed a lower clearance of rVIII-SingleChain (1.9 vs. 2.1 dL/h) and a longer half-life both in adolescents/adults (n = 28) and pediatric (n = 6) patients (15.5 and 11.9 hours, respectively vs. 14.5 and 10.3 hours) than previously reported.Conclusions Patients who switched to rVIII-SingleChain prophylaxis demonstrated excellent bleed control and a reduction in infusion frequency. A population PK analysis revealed improved PK parameters compared with those reported in the clinical trial.
Keywords: factor VIII; extended half-life; hemophilia A; pharmacokinetic; outcome